ПРАГМАТИЧЕСКОЕ ИЗУЧЕНИЕ ХУДОЖЕСТВЕННО-ИЗОБРАЗИТЕЛЬНЫХ ВЫРАЖЕНИЙ ПРИ ОПИСАНИИ ПЕРСОНАЖЕЙ В ТЕКСТЕ «БАБУРНАМЕ» (Scientific journal of the Fergana State University, 2023)
This article is devoted to the fact that when describing the character of images, each of the actions of its object on the way of observation, together with the indication of their positive or negative qualities, until they show what profession, what could come, in what area of skill, the skill of the image and reveal them more brightly through artistic images.